The effects of social media influencers, social media advertising, e-wom, and lifestyle towards purchase intention and brand image as a moderating variable in e-groceries - Handjaja, Joel Ezer; Triyanti, Anjeng Mustika; Anggraeni, Adilla; Putti, Aqillah Aeriza (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2023)
Social media has developed into an exceptional tool for everyone to generate marketing goods, services, and information sharing. This evolution of digital marketing is called eWOM, and it has created a new profession for users known as social media influencers. This research strives to demonstrate the effectiveness of influencers, advertisements, eWOM, and lifestyle as tools to build brand strength and purchase intention of ASTRO (Indonesia’s first quick commerce company that delivers groceries and essentials within 15 minutes). This empirical study utilized a quantitative research method and distributed questionnaires to the respondents. The study found that brand image and purchase intention have a significant impact on consumer behavior, while social media advertising, influencers, and eWOM have less of an impact.